Cybersecurity: Safeguarding the digital landscape - Kaur, Kiranjeet; Batth, Jaspreet Singh (AIP conference proceedings, 2024)
This paper examines the crucial subject of cyber security and its relevance in the current digital age. With the accelerated development of technology and interconnection, it is now more important than ever to guard against cyber attacks. The article gives a general overview of cyber security, including its meaning and value in protecting people, businesses, and societyat large. It explores a range of cyber threats, including insider threats, phishing scams, and malware assaults. The study then addresses crucial cyber security elements, such as identity and access management, network security, data protection, and application security. It looks at the techniques and recommendations used to improve cyber security, including encryption, firewalls, secure coding techniques, and incident response strategy. The study also examines recent developments in cyber security, such as IoT security, cloud security, and privacy laws. It addresses social engineering assaults and the significance of user education and awareness while emphasising the human element incyber security. The study also emphasizes the value of public-private partnerships, regulatory frameworks, and international collaboration in enhancing cyber security. Finally, it examines the field’s potential future developments, including automation, threat intelligence, and ethical issues. In order to effectively address cyber threats, the study emphasizes the dynamic nature of cyber security and the necessity for continual awareness and agility.